2023
DOI: 10.1109/lra.2023.3234771
|View full text |Cite
|
Sign up to set email alerts
|

SCENE: Reasoning About Traffic Scenes Using Heterogeneous Graph Neural Networks

Abstract: Understanding traffic scenes requires considering heterogeneous information about dynamic agents and the static infrastructure. In this work we propose SCENE, a methodology to encode diverse traffic scenes in heterogeneous graphs and to reason about these graphs using a heterogeneous Graph Neural Network encoder and task-specific decoders. The heterogeneous graphs, whose structures are defined by an ontology, consist of different nodes with type-specific node features and different relations with type-specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We evaluated the effectiveness of the proposed method with various GNN architectures. While we used 5-Layer GIN as the GNN architecture in the main experiments, we explored the suitability of other commonly used GNN architectures that are capable of handling edge features: MPNN, graph attention network (GAT), , graph transformer network (GTN), and 3-Layer GIN. Table S2 presents the predictive performance of pretrained GNNs using these architectures on the METLIN-SMRT data set.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the effectiveness of the proposed method with various GNN architectures. While we used 5-Layer GIN as the GNN architecture in the main experiments, we explored the suitability of other commonly used GNN architectures that are capable of handling edge features: MPNN, graph attention network (GAT), , graph transformer network (GTN), and 3-Layer GIN. Table S2 presents the predictive performance of pretrained GNNs using these architectures on the METLIN-SMRT data set.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the rejection method is very effective regarding safety considerations. For future work, a more sophisticated approach could use a generic graph encoding [24] and formulate the TL2LA task as link prediction in graphs.…”
Section: Discussionmentioning
confidence: 99%
“…The publicly available source code of our navigation map API for Argoverse enables other researchers to develop and evaluate their own navigation map-based approaches for motion prediction with ease. It remains to be investigated whether similar results are achievable using navigation maps in other HD map-reliant application areas beyond motion prediction, for instance traffic scene reasoning [35].…”
Section: Discussionmentioning
confidence: 99%